Strengthening Maternal Self-Care Through An Integrated Holisticare Model Of Reproductive Health Education And Herbal Heat-Pack To Improve Pregnancy Adaptation Among Primigravida Mothers In Ciseureuh Assisted Village, Purwakarta Regency, Indonesia - Shanti Hekmawati; Deka Friska (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Pregnancy adaptation is a complex biopsychosocial process that requires adequate maternal self-care. Primigravida mothers frequently experience physical discomfort, anxiety, limited reproductive health knowledge, and insufficient skills to manage pregnancy-related changes. Integrating reproductive health education with complementary non-pharmacological therapy may improve maternal adaptation and well-being. Objective: This study evaluated the effectiveness of the Integrated Holisticare Model, combining reproductive health education and Herbal Heat-Pack therapy, in strengthening maternal self-care and improving pregnancy adaptation among primigravida mothers. Methods: A sequential explanatory mixed-methods study was conducted in Ciseureuh Assisted Village, Purwakarta Regency, Indonesia, in 2026. The quantitative phase employed a quasi-experimental pretest–posttest control group design involving intervention and control groups. Participants in the intervention group received structured reproductive health education integrated with Herbal Heat-Pack therapy. Maternal self-care and pregnancy adaptation were assessed using validated instruments before and after the intervention, while qualitative interviews explored participants' experiences. Results: The Integrated Holisticare Model significantly improved maternal self-care, reproductive health knowledge, confidence, psychological readiness, and pregnancy adaptation compared with the control group. Participants also reported reduced physical discomfort, lower anxiety, and high acceptance of the intervention because it was practical, culturally appropriate, and easy to apply at home. Conclusion: The Integrated Holisticare Model is an effective community-based intervention for enhancing maternal self-care and promoting holistic pregnancy adaptation among primigravida mothers.